Desarrollo de las conciencias lingüísticas a través de la expresión artística en los niños y niñas de primer año de educación básica de la Unidad Eucativa Elvira Ortega, de la provincia de Cotopaxi, cantón Latacunga en la parroquia La Matriz en el año lectivo 2014-2015 - Cando Pruna, María Jenny (2015)
The present investigation was done to introduce a linguistic awareness manual by means of artistry expression in order to improve the teaching learning process in every child, allowing teachers to take better decisions using creativity and the execution of distinct activities, which children use to improve their environment in which they interact, this is help the child to develop confidence and save so that it will be possible to socialize and to be participants in the society where they can develop and acquire decision taking, which will help them in their daily life.With the execution of this project, it was possible to involve teachers and authorities to include in their syllabus ways and manners of educating, these strategies are creative and develop imagination in the corporal expression as well as in artistry expression, and language since it will be able to transmit a clear and efficient message of the knowledge that is expected to be taught so that the information can be meaningful and useful so that children be capable and solvent people who are able to face any difficulty that come in the future thus achieving their established goal .